ANALYZING STUDENTS' ABILITIES AS PROSPECTIVE TEACHERS OF MATHEMATICS IN CONSTRUCTING PROOFS - Soffil Widadah; Dwi Juniati (JME (Journal of Mathematics Education), 2023)
Mathematical proof demands accuracy and precision in formulating correct and logical arguments. Students need to develop their ability to produce accurate and precise proofs. This study aims to analyze the ability of prospective mathematics teachers in constructing geometry and algebraic proofs. The research subjects were 8 prospective mathematics teacher students, four male and four female. This descriptive qualitative research begins with giving tests to research subjects, and then we conduct interviews. The results showed that male students were better at compiling geometry than algebraic proofs. At the same time, female students are better at compiling algebraic proofs than in geometry. This result is due to the spatial ability of men better than women. When compiling geometry proofs, apply procedural, syntactic, and semantic proofs. When compiling algebraic proofs, only apply procedural proofs. Female students, when compiling geometry proofs, only apply procedural proofs. When compiling algebraic proofs, they apply procedural proofs and syntactic proofs.